Solve the equation g2 – 12g = –36 A. g = –6 B. g = 6 C. g = –3, g = 4 D. g = –6, g = 6

Question

Solve the equation g2 – 12g = –36

A. g = –6
B. g = 6
C. g = –3, g = 4
D. g = –6, g = 6

in progress 0
1 week 2021-10-12T08:52:05+00:00 2 Answers 0

Answers ( )

    0
    2021-10-12T08:53:26+00:00

    Your answer is B. G=6

    0
    2021-10-12T08:53:44+00:00

    Answer:

    g=6

    Step-by-step explanation:

    g^{2} -12=-36\\g^{2} -12+36\\ (g-6)(g-6)\\ g-6=0\\ g=6

Leave an answer

Browse
Browse

27:3+15-4x7+3-1=? ( )